Üstkurmaca Bir Metin: Kayıp Hikayeci - Tural, Şecaattin (Gökkubbe, 2005)
Alim Kahraman'ın birbirıne bağlı hikayelerden oluşan "Kayıp Hikayeci"si hikayecinin kaybolması, yarım bırakılmış metin olma özelliği, yabancılaşmayı, kimlik ve kişilik bölünmesini metaforik/imgesel düzlemde dile getirmesi, içerik yerine biçimi öne çıkarması, kuramsal sorunları metne taşımasıyla kurgunun serüveni denilen üstkurmaca bir metin olarak bu makalenin konusunu oluşturmuştur. "Alim Kahraman's Missing Story Writer" consists of stories that connected to one another. Those stories contain, missing of the story writer, being untinıshed text, being allianed, division of charecter and identy are expressed metaphorically and imagerically: importance of style than contend, discussion of theorical problems. All these are the qualities of metafiction. This article examines the Missing Story Writer from this point of view.
A Metafiction Text: Missing Story Writer
Keywords: Modern Türk Hikayeciliği; Alim Kahraman; Kayıp Hikayeci; Üstkurmaca Metin; Modern Turkish Short Story; Metafiction Text